2019
DOI: 10.1177/1358863x18824650
|View full text |Cite
|
Sign up to set email alerts
|

National trends and outcomes for extra-corporeal membrane oxygenation use in high-risk pulmonary embolism

Abstract: Little is known about the temporal trends and outcomes for extra-corporeal membrane oxygenation (ECMO) in patients with high-risk pulmonary embolism (PE) in the United States. We queried the National Inpatient Sample (NIS) database from 2005 to 2013 to identify patients admitted with high-risk PE. Our objective was to determine trends for ECMO use in patients with high-risk PE. We also assessed in-hospital outcomes among patients with high-risk PE receiving ECMO. We evaluated 77,809 hospitalizations for high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 23 publications
1
48
1
Order By: Relevance
“…In a retrospective study of 219 high-risk patients who were treated with ECMO, the majority of patients were male (67%) and female sex was found to be an independent predictor of mortality (OR, 2.19; 95% CI, 1.03-4.67), suggesting that women may be less likely to receive ECMO and women who do may have higher mortality. 102 DOACs have rapidly become the most common oral anticoagulant therapy for PE, replacing VKA in most situations, given their clinical efficacy and relative ease of administration. 103 The benefits of DOACs appear to be similar for men and women; there are no sex differences in the rates of recurrent VTE for patients on DOAC treatment.…”
Section: Treatment and Outcomes Of High-risk Pementioning
confidence: 99%
“…In a retrospective study of 219 high-risk patients who were treated with ECMO, the majority of patients were male (67%) and female sex was found to be an independent predictor of mortality (OR, 2.19; 95% CI, 1.03-4.67), suggesting that women may be less likely to receive ECMO and women who do may have higher mortality. 102 DOACs have rapidly become the most common oral anticoagulant therapy for PE, replacing VKA in most situations, given their clinical efficacy and relative ease of administration. 103 The benefits of DOACs appear to be similar for men and women; there are no sex differences in the rates of recurrent VTE for patients on DOAC treatment.…”
Section: Treatment and Outcomes Of High-risk Pementioning
confidence: 99%
“…Among the 421 studies identified by the search strategy, 106 studies were deemed eligible and 21 studies were eventually included in the analysis, for a total population of 635 patients with acute high‐risk PE receiving ECMO support 11‐31 . Exclusion reasons were: overlapping populations ( n = 10), studies not focused on ECMO use in PE ( n = 4), commentary papers ( n = 3), studies not reporting outcome of interest ( n = 1), and case reports/cases series including < 4 patients ( n = 67).…”
Section: Resultsmentioning
confidence: 99%
“…In massive PE, where blood pressure can be barely detectable, instigation of ECMO at the earliest timepoint appears to be a sound concept 35–37 . The failing heart does not fail purely because of afterload mechanics.…”
Section: What Is Needed Nowmentioning
confidence: 99%
“…The downsides of this, of course, include the nature of definitive treatment in this situation, which typically includes the use of systemic thrombolysis in the presence of large bore cannulae inserted into central veins in an unstable patient, with bleed risks apparent 35 . In an effort to minimize bleeding complications, ECMO could be combined with low-dose CDT to stabilize the sickest of PE patients, rather than considering full-dose systemic thrombolytic 36 …”
Section: What Is Needed Nowmentioning
confidence: 99%